Overview of Three Proliferation Pathways (Wnt, Notch, and Hippo) in Intestine and Immune System and Their Role in Inflammatory Bowel Diseases (IBDs) - Khoramjoo, Seyed Mobin; Kazemifard, Nesa; Baradaran Ghavami, Shaghayegh; Farmani, Maryam; Shahrokh, Shabnam; Asadzadeh Aghdaei, Hamid; Sherkat, Ghazal; Zali, Mohammad Reza (Frontiers in Medicine, 2022)
Inflammatory Bowel Disease (IBD) is a chronic disorder of gastrointestinal tract which consists of Crohn’s disease (CD) and Ulcerative Colitis (UC). The etiology of this disease is not yet clear and hence there are numerous medications and treatments for IBD patients, a definite and permanent treatment is still missing. Therefore, finding novel therapeutic approaches is vital for curing IBD patients. In gastrointestinal tract, there are various lineages of cells with different roles. Existence of all of them is necessary for the barrier function of the intestinal epithelial cells. Therefore, signaling pathways which control the hemostasis of intestine such as Wnt, Notch and Hippo play important roles in achieving the balance among different cell linages there. Additionally, these signaling pathways act as a regulator of cell growth, tissue homoeostasis and organ size. In patients with IBD, recent studies have revealed that these signaling pathways are dysregulated that it could result in depletion or excess of a cell lineage in intestine. Moreover, dysregulation of these signaling pathways in cell lineages of immune system could lead to dysregulation of immune system’s responses in IBD. In this review, we summarized the components and signaling of each pathway and their role in intestine and immune system. Furthermore, we reviewed latest scientific literatures on the engagement of them in the pathogenesis of IBD. An overview of these three signaling pathways and their interaction together and IBD could provide a novel insight into prospective research directions and focus for finding efficient medications or treatments.